2015
DOI: 10.1103/physrevlett.114.105502
|View full text |Cite
|
Sign up to set email alerts
|

Competing Kinetics and He Bubble Morphology in W

Abstract: The growth process of He bubbles in W is investigated using molecular dynamics and parallel replica dynamics for growth rates spanning 6 orders of magnitude. Fast and slow growth regimes are defined relative to typical diffusion hopping times of W interstitials around the He bubble. Slow growth rates allow the diffusion of interstitials around the bubble, favoring the biased growth of the bubble towards the surface. In contrast, at fast growth rates interstitials do not have time to diffuse around the bubble, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(80 citation statements)
references
References 35 publications
3
77
0
Order By: Relevance
“…The energy barrier for nucleation is thus expected to decrease due to the presence of other interstitials, while that of annihilation will increase, as it entails “unbinding” an interstitial. This is consistent with the tendency of Frenkel pair nucleations to occur in the vicinity of pre-existing interstitials that was previously observed in long-timescale simulations of bubble growth 22 . Analysis of the current simulations further shows that nucleation and annihilation tend to occur in a way that leaves the vacancy clusters as compact as possible, i.e., so as to maximize the number of vacancy first neighbors.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The energy barrier for nucleation is thus expected to decrease due to the presence of other interstitials, while that of annihilation will increase, as it entails “unbinding” an interstitial. This is consistent with the tendency of Frenkel pair nucleations to occur in the vicinity of pre-existing interstitials that was previously observed in long-timescale simulations of bubble growth 22 . Analysis of the current simulations further shows that nucleation and annihilation tend to occur in a way that leaves the vacancy clusters as compact as possible, i.e., so as to maximize the number of vacancy first neighbors.…”
Section: Resultssupporting
confidence: 91%
“…As this process repeats following the absorption of additional He atoms, the excess interstitials accumulate around the bubble. These are eventually released, often in the form of small prismatic dislocation loops, a process referred to as loop punching 22, 3640 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hu et al [13] studied the trap mutation and dissociation of He clusters in the near-surface region of tungsten, which has significant impact on the W surface morphology and near-surface structure. More recently, Sandoval et al [14] have studied the growth process of He bubbles in W and found that the evolution of surface morphology is very sensitive to the growth rate of He bubbles. The above studies imply that He bubbles are necessary for the initiation of fuzz formation in W bulk.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the dynamics of helium bubbles play an important role in determining the mechanical performance of metals. As a result, significant efforts have been made to understand the evolution of helium bubbles under thermal annealing, radiation, or mechanical loading [8][9][10][11][12][13][14][15][16].…”
mentioning
confidence: 99%